2020
DOI: 10.3390/foods9111716
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Fruit by-Products as Bioactive Compounds for Intestinal Health

Abstract: The fruit processing industry generates large amounts of wastes (pomace, seeds, peels) that causes negative environmental impact with considerable treatment expenses. Nevertheless, various studies demonstrated that these by-products are still rich in bioactive compounds, especially dietary fibres and phenolic compounds, thus leading to significant chemical, physical and biological properties. These characteristics make fruits by-products a good source for new supplements in food products having important effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(21 citation statements)
references
References 147 publications
1
19
0
1
Order By: Relevance
“…The major compounds of clementine essential oils were D-Limonene 66.88%, while the dominant components clementine essential oils were Diethyl malate 6.79 % and Linalool 5.25%, Geranial and α-Terpinene (1.66 and 1.62%) were identified by the GC/MS analyses (Table 1). It has been found by Zhang et al and Chaouch et al 16,8 that the yield of citrus essential oils in most of the cases ranged from 0.2-2.0% which is following our results. It has been found by Chen et al 17 that the total oil yield from sweet orange 0.80%, eureka lemon 0.90%, and mandarin 0.80% which were lower than our results.…”
Section: Results and Discussion: Essential Oils Composition Of Clemen...supporting
confidence: 92%
“…The major compounds of clementine essential oils were D-Limonene 66.88%, while the dominant components clementine essential oils were Diethyl malate 6.79 % and Linalool 5.25%, Geranial and α-Terpinene (1.66 and 1.62%) were identified by the GC/MS analyses (Table 1). It has been found by Zhang et al and Chaouch et al 16,8 that the yield of citrus essential oils in most of the cases ranged from 0.2-2.0% which is following our results. It has been found by Chen et al 17 that the total oil yield from sweet orange 0.80%, eureka lemon 0.90%, and mandarin 0.80% which were lower than our results.…”
Section: Results and Discussion: Essential Oils Composition Of Clemen...supporting
confidence: 92%
“…Numerous studies have shown that waste from fruit processing has a high content of bioactive compounds with high antioxidant capacity [16,17], with a beneficial role on human health [18][19][20]. International scientific research has focused on the characterization of fruit by-products and their further incorporation for the development of functional foods and beverages [21].…”
Section: Introductionmentioning
confidence: 99%
“…The most common key compounds from F&V by-products are polyphenols ( Figure 1 : phenolic acids and their polymeric derivatives, such as lignans, stilbenes, tannins, and flavonoids) in skins, pulp, seeds, or pomace [ 24 ]. Phenolic acids are common in F&V by-products such as apple pomace (chlorogenic acid, and cryptochlorogenic acid) [ 25 ], artichoke (bracts, leaves and stems) (chlorogenic acid) [ 26 ], mango kernel and leaves (gallic acid, and ellagic acid) [ 27 ], pomegranate peel (caffeic acid, chlorogenic acid, ellagic acid, and gallic acid) [ 28 ], potato peel (chlorogenic acid, ferulic, gallic, protocatechuic and caffeic acid) [ 29 ], tomato peel (3-caffeoylquinic acid, 5-caffeoylquinic acid, 3,4-di-O-caffeoylquinic acid, and 3,4,5-tri-caffeoylquinic acid) [ 30 ] and blueberry pomace (cinnamic acid derivatives) [ 22 , 31 , 32 , 33 ]. Among flavonoids, flavones, flavanones, anthocyanidins, and flavonols can be found in grape pomace (catechins, anthocyanins, stilbenes, and flavonol glycosides), onion skin (quercetin 3,40-O-diglucoside and quercetin 4-o-monoglucoside and isorhamnetin-3-glucoside) [ 34 ], tomato peel (lycopene, naringenin chalcone and naringenin) [ 30 ], apple pomace (hydroxycinnamates, phloretin glycosides, quercetin glycosides, catechins, procyanidins, and epicatechin) [ 25 ], figs peel (cyanidin-3-rutinoside, cyanidin-3,5-diglucoside, cyanidin-3-O-diglucoside, epitecatechin, catechin and quercetin-rutinoside) [ 32 ], blueberry pomace (anthocyanins and flavonol-glycosides) [ 33 ], and citrus peel (eriocitrin, hesperidin, and naringin) [ 22 , 31 , 32 , 35 ].…”
Section: Fruit and Vegetables By-products As A Source Of Valuable Compoundsmentioning
confidence: 99%